TEOREMA TITIK TETAP UNTUK DUA PEMETAAN DI RUANG METRIK CONE RECTANGULAR - Sunarsini Sunarsini; Sadjidon Sadjidon; Sie Evan Setiawan (UNEJ e-Proceeding, 2022)
Azam introduced the concept of a rectangular cone metric space in 2009. By adding the rectangular property to the cone metric function, we get the definition of a rectangular cone metric space. The purpose of this paper is to discuss the development of a fixed point Banach contraction mapping in a rectangular cone metric space. In particular, we prove the Banach Fixed Point Theorem for two self-mappings on the space with an alternative proof. Furthermore, we provide related examples to make it easier to understand the theorem. Keywords: Fixed point Banach, rectangular cone metric space, two-self mappings